2008
DOI: 10.1038/modpathol.3800992
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA mutations in the kinase domain (exon 20) of uterine endometrial adenocarcinomas are associated with adverse prognostic parameters

Abstract: Mutations of the oncogene PIK3CA occur frequently in endometrial carcinomas, but their prognostic significance is unclear. To determine the clinicopathological and molecular implications of these mutations, PIK3CA status was investigated in 109 endometrial (102 endometrioid and 7 mixed) carcinomas and the results were compared with clinicopathological parameters associated with prognosis. Tumors were also investigated for microsatellite instability and PTEN, b-catenin gene (CTNNB1), K-RAS, and B-RAF mutations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
79
6
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 32 publications
9
79
6
1
Order By: Relevance
“…We have investigated recently the PIK3CA status in a large series of endometrioid adenocarcinomas and compared the results with the clinical and pathologic parameters associated with prognosis. 16 In our series, the PIK3CA mutations occurred in 29% of endometrioid adenocarcinomas, all with myometrial invasion. We also found that histologic type, grade, and depth of myometrial invasion varied significantly depending on the location of PIK3CA mutations, either in exon 9 or exon 20.…”
mentioning
confidence: 49%
See 4 more Smart Citations
“…We have investigated recently the PIK3CA status in a large series of endometrioid adenocarcinomas and compared the results with the clinical and pathologic parameters associated with prognosis. 16 In our series, the PIK3CA mutations occurred in 29% of endometrioid adenocarcinomas, all with myometrial invasion. We also found that histologic type, grade, and depth of myometrial invasion varied significantly depending on the location of PIK3CA mutations, either in exon 9 or exon 20.…”
mentioning
confidence: 49%
“…16 Of the 30 highgrade carcinomas included in this study, the PIK3CA mutations were found in 21% (3/14) nonendometrioid adenocarcinomas and in 44% (7/16) mixed endometrioid adenocarcinomas-non-endometrioid adenocarcinomas. All the PIK3CA mutations found in non-endometrioid adenocarcinomas and in mixed carcinomas occurred in exon 20 ( Figure 1).…”
Section: Pik3ca Mutations and Gene Expressionmentioning
confidence: 80%
See 3 more Smart Citations